KENAKALAN REMAJA - Rahman Taufiqrianto Dako (Jurnal Inovasi, 2012)
Agree or not, adolescent era is a gratify era. In this era, activities of adolescents are only playful. Not all of theirs, however, could feel it. The aim of this papers is to describe juvenile delinquency and its factors. Some factors of juvenile delinquency can be family, freinds, school/environtment society, and mass media. Key words: juvenile delinquency, its factors.